2010
DOI: 10.1186/1756-9966-29-18
|View full text |Cite
|
Sign up to set email alerts
|

Association between C282Y and H63D mutations of the HFE gene with hepatocellular carcinoma in European populations: a meta-analysis

Abstract: BackgroundHereditary hemochromatosis (HH) is an autosomal recessive disorder mainly associated with homozygosity for the C282Y and H63D mutations in the hemochromatosis (HFE) gene. The reports about the C282Y and H63D mutations and hepatocellular carninoma (HCC) were controversial. To clarify the relationship between C282Y and H63D mutations and HCC, a meta-analysis including nine studies (1102 HCC cases and 3766 controls, mainly came from European populations) was performed.MethodsThe association was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…In patients with chronic liver disease and mild iron overload, conflicting results concerning a possible association between HFE status and HCC have been reported (Table 2). [12][13][14][15] In a prospective study of 301 consecutive patients with cirrhosis, it was found that liver iron overload and heterozygosity for the C282Y HFE mutation were associated with a higher risk of HCC in patients with alcoholic Experimental models, humans Figure 2 The role of iron in liver disease. Oxidative stress in the liver can be induced by HCV, alcohol, NASH, hemochromatosis, and inflammation.…”
Section: Iron As a Cofactor In The Pathogenesis Of Hccmentioning
confidence: 99%
“…In patients with chronic liver disease and mild iron overload, conflicting results concerning a possible association between HFE status and HCC have been reported (Table 2). [12][13][14][15] In a prospective study of 301 consecutive patients with cirrhosis, it was found that liver iron overload and heterozygosity for the C282Y HFE mutation were associated with a higher risk of HCC in patients with alcoholic Experimental models, humans Figure 2 The role of iron in liver disease. Oxidative stress in the liver can be induced by HCV, alcohol, NASH, hemochromatosis, and inflammation.…”
Section: Iron As a Cofactor In The Pathogenesis Of Hccmentioning
confidence: 99%
“…Evidence from an updated meta-analysis of 24 individual case-control studies from 23 publications suggested that null genotypes of both GSTM1 and GSTT1 were associated with increased HCC risk in Asians, and individuals with the dual null genotype of GSTM1/GSTT1 were particularly susceptible to developing HCC (Wang et al, 2010). A meta-analysis including nine studies (1102 HCC cases and 3766 controls) conducted by Jin et al (2010) showed that the C282Y mutation was associated with HCC in European alcoholic liver cirrhosis patients. TNF-a 308 G/A polymorphism was associated with many other cancers, which was consistent with our study.…”
Section: Shi and Dumentioning
confidence: 97%
“…According to a recent meta-analysis, individuals carrying the C282Y hemochromatosis mutation have an increased risk of hepatocellular carcinoma (112). Regarding extra-hepatic malignancies in the general population, there were some studies cited in NNR4 indicating an increased risk of colon cancer and also other cancers related to high iron stores.…”
Section: Cancermentioning
confidence: 99%